Визначення пікової потужності міського автобуса в реальних режимах руху - Сітовський, Олег; Дембіцький, Валерій (Видавництво Львівської політехніки, 2018)
To improve the efficiency of ICE must create hybrid. To achieve maximum efficiency of a hybrid power unit it is necessary to develop optimal algorithms for controlling the units and units of the vehicle. Research was conducted to determine the engine's peak power and the average power ICE of the route was set.
Determination of peak power of city bus in real traffic
Keywords: 629.3